2017
DOI: 10.3390/catal7090261
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Sinergy of MW Irradiation and Ionic Liquids in Catalysis of Organic Reactions

Abstract: Abstract:The quest for sustainable processes is becoming more and more important, with catalysis playing a major role in improving atom economy and reducing waste. Organic syntheses with less need of protecting/de-protecting steps are highly desirable. The combination of microwave irradiation, as energy source, with ionic liquids, as both solvents and catalysts, offered interesting solutions in recent years. The literature data of the last 15 years concerning selected reactions are presented, highlighting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 177 publications
(233 reference statements)
0
7
0
Order By: Relevance
“…In both cases, no reaction was observed. Inspired by the excellent results achieved in previous studies [32,38,39], a hydrophobic ionic liquid (i.e., [pmim]Tf 2 N 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) was adopted as co-solvent. In fact, in the last years ionic liquids became a valid alternative to the conventional molecular solvents, due to their unique properties such as non-volatility, high thermal stability and reusability [40].…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, no reaction was observed. Inspired by the excellent results achieved in previous studies [32,38,39], a hydrophobic ionic liquid (i.e., [pmim]Tf 2 N 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) was adopted as co-solvent. In fact, in the last years ionic liquids became a valid alternative to the conventional molecular solvents, due to their unique properties such as non-volatility, high thermal stability and reusability [40].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, with the idea to further investigate the potentiality of our catalytic system, we decided to exploit the microwave irradiation as energy source for the ECODS, to optimize the reaction time as much as possible. On the other hand, the combination of microwave irradiation, as energy source, with ionic liquids, either as solvents or catalysts, has been largely investigated, in recent years [26].…”
Section: Catalytic Ecods Of the Model Diesel Under Mwmentioning
confidence: 99%
“…1,3–12 There are dozens of specialised reviews on the use of ILs and derivatives in catalysis reported in the last decade. 13–37 We will concentrate on the possibilities and advantages that ILs and their derivatives may provide for green catalytic reactions as compared to classical molecular organic solvents or water. Indeed, ILs may offer the possibility of:…”
Section: Introductionmentioning
confidence: 99%